2018
DOI: 10.1016/j.exger.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and muscle weakness: A two-way relation?

Abstract: The potential association between depressive symptoms and dynapenia - i.e. muscle weakness - is limited to few, mainly cross-sectional, studies. We use SHARE (Survey on Health, Ageing and Retirement in Europe) panel data to investigate whether the onset of dynapenia at 4-year follow-up can be explained by pre-existing (either at baseline, or at 2-year follow-up) depressive symptoms, or vice versa. Depressive symptoms were identified as a score of 4 or more on the 12-item EURO-D scale. Individuals were classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
2
21
0
1
Order By: Relevance
“…A nationally representative sample of Brazilians aged 65 years and older using the same cut-off values as our study observed a higher prevalence of low muscle strength (28.2%) [18]. Other studies which applied the older cut off values defined by the European Working Group on Sarcopenia in Older People (EWGSOP), observed a higher prevalence of low muscle strength of 33.9% among Mexican people 50 years and older [39], 22.5% among Europeans aged 70 years and older [40], 44% in a population of Americans aged 65 years and older [41]…”
Section: Prevalence Of Obesity Low Muscle Strength and Low Muscle Masssupporting
confidence: 69%
See 1 more Smart Citation
“…A nationally representative sample of Brazilians aged 65 years and older using the same cut-off values as our study observed a higher prevalence of low muscle strength (28.2%) [18]. Other studies which applied the older cut off values defined by the European Working Group on Sarcopenia in Older People (EWGSOP), observed a higher prevalence of low muscle strength of 33.9% among Mexican people 50 years and older [39], 22.5% among Europeans aged 70 years and older [40], 44% in a population of Americans aged 65 years and older [41]…”
Section: Prevalence Of Obesity Low Muscle Strength and Low Muscle Masssupporting
confidence: 69%
“…A nationally representative sample of Brazilians aged 65 years and older using the same cut-off values as our study observed a higher prevalence of low muscle strength (28.2%) [ 18 ]. Other studies which applied the older cut off values defined by the European Working Group on Sarcopenia in Older People (EWGSOP), observed a higher prevalence of low muscle strength of 33.9% among Mexican people 50 years and older [ 39 ], 22.5% among Europeans aged 70 years and older [ 40 ], 44% in a population of Americans aged 65 years and older [ 41 ] and 71% in a community-dwelling older New Zealanders aged 75 years and older [ 42 ]. The higher prevalence observed in these groups, is possibly explained by the inclusion of people older than 74 years, and a potentially less healthy population than those participants included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, significant inequalities have been found regarding this condition 1 , meaning that individuals of lower socioeconomic levels are negatively impacted 11 . Accordingly, the maintenance of muscle strength while aging has high clinical significance 14 because dynapenia is associated with disability 10,15 and chronic diseases 16 , independent of muscle mass.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding dynapenia distribution in the population, literature shows that its prevalence varies depending on setting, definition used and individuals' characteristics, such as health conditions, ranging from 17.8% in the European population aged 70 and older 16 , to 71.2% in a fracture clinic in Colombia 17 . Most studies on dynapenia have been conducted in developed countries, lacking studies regarding its prevalence and correlates in developing countries 10,11,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Dass die physische Gesundheit für die mentale Gesundheit von Bedeutung ist, lässt sich einfach nachvollziehen, nicht nur anhand von schweren Erkrankungen, die die Lebensqualität einschränken oder mit denen eine geringe Überlebenswahrscheinlichkeit einhergeht. Dass psychische Probleme für physische Krankheiten eine Rolle spielen ist hingegen weniger intuitiv, aber durch eine Vielzahl an Studien bestätigt (Bertoni et al 2018;Penninx 1998;Hays et al 1997). Auch in den hier durchgeführten Analysen wird dies deutlich.…”
Section: Diskussionunclassified